1965
DOI: 10.1083/jcb.25.2.191
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS OF CELLULOSE BY ACETOBACTER XYLINUM

Abstract: The transfer of the glucosyl moiety from uridine diphosphate glucose in the presence of Acetobacter xylinum cell-free extracts led to the formation of a mixture of alkali-soluble and -insoluble cellodextrins. Typical cellulose fibrils could not be detected by electron microscopy in this product. Immediately after release into the medium, cellulose formed by whole cells is in a "prefibrous" form which passes through Millipore filters of 0.45 and 0.8 # pore diameter. Non-filtrable fibrils arise from this materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This may be because the added CMC in static culture had delayed the aggregation and the crystallization of cellulose microfibrils, and resulted in the crystallite index and cellulose I content decreased. This confirmed that added polysaccharides and hemicelluloses can interact with the BC microfibrils and change its morphology [15][16][17]. …”
Section: B Morphologysupporting
confidence: 54%
“…This may be because the added CMC in static culture had delayed the aggregation and the crystallization of cellulose microfibrils, and resulted in the crystallite index and cellulose I content decreased. This confirmed that added polysaccharides and hemicelluloses can interact with the BC microfibrils and change its morphology [15][16][17]. …”
Section: B Morphologysupporting
confidence: 54%
“…Besides interconnecting functions, the sulfated glucan could also modulate cellulose assembly and control its orientation. Such effects have been inferred from results obtained with composites of cellulose synthesized by the bacterium A. xylinum in the presence of anionic or neutral cellulosic derivatives (Ben‐Hayyim and Ohad 1965, Haigler et al 1982, Yamamoto et al 1996). Additionally, the sulfated glucan may also be at the interface of cellulose fibrils and the matrix galactans.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxymethylcellulose sodium salt (CMC), which is known as a water soluble polysaccharide, was employed to add to the Schramm-Hestrin (SH) medium (Hestrin & Schramm, 1954) used for the cultivation of A. xylinum. The CMC could be considered as an inhibitor for self-assembly of secreted cellulose microfibrils by the surface electrostatic repulsion due to the carboxymethyl groups of attached CMC (Ben-Hayyim & Ohad, 1965;Watanabe, Gondo, & Kitao, 2004). Concerning the condition of the templates, the surface properties of NOC were modified by changing the draw ratio, and also addition of chitin as an additive.…”
Section: Introductionmentioning
confidence: 99%